Short term variability in FEV1: relation to pretest activity, level of FEV1, and smoking habits. Issue 12 (December 1984) - Tweeddale, P M; Merchant, S; Leslie, M; Alexander, F; McHardy, G J
Abstract : The natural variability in forced expiratory volume in one second (FEV1) over 20 minutes was determined in 54 fit hospital employees and 13 patients with restrictive lung disorders. Initial FEV1 ranged from 1.1 to 6.3 1 BTPS. Variability when expressed as absolute change was similar at all levels of FEV1, so that, when expressed as percentage change, variability decreased with increasing FEV1. Smoking habits did not appear to affect variability but activity before the test did. On the basis of these results an absolute change in FEV1 of 190 ml would be necessary for 95% confidence that the change in FEV1 occurred other than by chance in any one individual. This suggests that the absolute change in FEV1 might be a more reliable criterion than percentage change when distinguishing between natural variability and a response to inhalation of bronchodilators.